The Effect of Metabolic Resistance Training (MRT) on Improving Muscle and Bone Density and wing Shooting Accuracy in Young Handball Players - Ahmed Shakir Al-khannaq; Baha Mohammed Taqi (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study explores how young wing handball players who are affected by Metabolic Resistance Training (MRT), an integration of resistance workouts and high-intensity cardio. The challenges faced by wing players are clear, needing not only physical stamina and strength but also accuracy when shooting from close quarters while the player jumping in the air. The participants' risk of injuries, such as bone stress and muscular strains, are increased by the frequent falls and different body positions that occur during the match. Therefore, increasing bone and muscle density are essential to reduce the risk of injuries while improving performance. Conventional training frequently fails to meet these needs. 12 wing handball players, ages 16 to 18, participated in this study using an experimental approach. Over the course of 8 weeks, they attended MRT sessions three times a week. To improve technical proficiency for this physically demanding position, the study intends to evaluate how MRT affects muscle and bone density as well as wing shooting accuracy.